A GENDER PERFORMATIVITY ANALYSIS ON GENDER NORMS PORTRAYED IN LOUISA MAY ALCOTT’S LITTLE WOMEN - Traesar, Livia; Sujiwa, Krisna (JOLALI: Journal of Language and Literature, 2025)
This research analyses gender norms and performativity in Louisa May Alcott's Little Women (1868) using Judith Butler's gender performativity theory. Alcott's semi-autobiographical portrayal of the March sisters paints a vivid picture of nineteenth-century American gender norms and their societal ramifications. This study focuses on Jo March and Theodore "Laurie" Lawrence and examines how their refusal to comply with standard gender norms reveals the performativity of gender. Jo, an outspoken and ambitious writer, and Laurie, a sensitive aspiring musician, are both subjected to social pressures to conform to traditional conceptions of femininity and masculinity, resulting in feelings of alienation and misfitting. By examining their problems, the research demonstrates how gender, as defined by societal and cultural assumptions, limits individual expression and imposes conformity. The study uses Butler's framework to show how Alcott's characters adopt gendered behaviors to fulfill society's expectations, emphasizing the tension between uniqueness and societal conventions. The research dives deeper into Alcott's subversion of preconceptions, as seen by Jo's rejection of traditional female roles and Laurie's challenges to masculine standards. Finally, this research emphasizes Little Women's ongoing importance as a critique of gender stereotypes and a reflection on the larger societal assumptions that shape identity. This study reinforces the importance of Alcott's work in conversations about gender performativity and societal expectations by locating it within feminist discourse.